ANALISIS PERKEMBANGAN PEMBANGUNAN BIDANG KESEHATAN PROVINSI BANTEN (Jurnal Manajemen Pembangunan Daerah, 2025)
ABSTRACT            The success of human resource development is measured by using the Human Development Index (HDI). HDI is calculated using three indicators: the health index projected in Life Expectancy (AHH), education index, and standard of living. The purpose of this study to analyze the condition of health development in Banten Province and formulate strategies to improve the health index of Banten Province. The method used in this research is descriptive analysis and SWOT analysis. The study on the health development conditions in the Province of Banten includes the achievements of health development through commonly used health indicators to measure the health development of a region, including Antenatal Care Coverage, Maternal and Infant Mortality Rates, and the availability of health facilities and medical personnel in the Province of Banten. The results of the SWOT analysis to improve the health index in the Province of Banten are: 1) Improving the quality of health development planning; 2) Improving the partnerships with private and business world and cooperation between central, provincial and district / city; 3) Improving the health policy and budgeting; 4) Implementing promotions and education related to healthy life and nutrition behavior, and improving the handling quality related issues; 5) Improving the quantity and quality of Social Security Administrator (BPJS) service recipients and 6) Improving the coordination with central government, district / city government, and community in implementing this health program.Keywords: Life expectancy (AHH), development, strategy, SWOT